2009
DOI: 10.1007/s10930-009-9204-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the 3-D Structure of a Recombinant Laccase from Trametes trogii Active at a pH Close to Neutrality

Abstract: A cDNA encoding a novel laccase from the white-rot fungus Trametes trogii was cloned and expressed in Pichia pastoris. The recombinant protein (Lcc2) exhibited kinetic parameters for both phenolic and non phenolic substrates that were different from the previously described Lcc1, the main laccase isoform expressed by T. trogii; in addition, the pH/activity profiles for phenolic substrates of Lcc2 were shifted upward by 1-1.5 pH units towards neutrality as compared to Lcc1. Comparative modeling of the two lacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In this work we used a PCR-based screening to clone four laccase coding sequences of T. trogii BAFC 463. Of these, sequences lcc1 and lcc2 encoded proteins with 100% and 99% identity with laccases LCC1 and LCC2 previously reported for T. trogii 201 [22,23] while lcc3 and lcc4 encoded two novel isoenzymes. Cloning and expression of sequence lcc3 in K. pastoris showed that it encodes a laccase with a functional signal peptide, capable of oxidizing the substrates ABTS and DMP with characteristic pH activity profiles and kinetic constants commonly observed for other fungal laccases, with higher catalytic efficiency for ABTS that for the phenolic substrate DMP (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this work we used a PCR-based screening to clone four laccase coding sequences of T. trogii BAFC 463. Of these, sequences lcc1 and lcc2 encoded proteins with 100% and 99% identity with laccases LCC1 and LCC2 previously reported for T. trogii 201 [22,23] while lcc3 and lcc4 encoded two novel isoenzymes. Cloning and expression of sequence lcc3 in K. pastoris showed that it encodes a laccase with a functional signal peptide, capable of oxidizing the substrates ABTS and DMP with characteristic pH activity profiles and kinetic constants commonly observed for other fungal laccases, with higher catalytic efficiency for ABTS that for the phenolic substrate DMP (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Sequence lcc1 (GenBank KU055621) encodes a protein with 100% amino acid identity with previously reported LCC1 of T. trogii strain 201 (GenBank CAC13040, [22]). Sequence lcc2 of T. trogii BAFC 463 (GenBank KU055622) encodes a protein with 99% amino acid identity with the reported sequence for LCC2 of T. trogii 201 (GenBank CAL23367, [23]), with 4 amino acid substitutions in mature translated protein sequence: D14N, I186L, A251 V, T433A (Fig. S1).…”
Section: Cloning Of Laccase Coding Sequences From T Trogii Bafc 463mentioning
confidence: 94%
See 1 more Smart Citation
“…However, the affinity for phenolic substrates decreased (being notably lower at this pH than at pH 5.0), with K m values being up to 4.2-and 4.7-fold higher for DMP and sinapic acid, respectively. At pH 5.0, deprotonation of a highly conserved aspartate residue (Asp206; side chain pK a , 3.9) that interacts with the reducing substrate at the T1 Cu site (9) may have contributed to this effect (19).…”
Section: Resultsmentioning
confidence: 99%